The Development of Human Embryos from a Modern Medical Perspective and the Qurʼān: A Bibliometric Analysis - Luqmi, Fitra Zahrotul; Kesuma, Aghesna Rahmatika; Nabilla; Eduard (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2026)
Human embryonic development constitutes one of the most intensively studied domains in biomedical science; however, interdisciplinary engagement connecting modern embryology with Qur'ānic descriptions of human creation remains markedly underrepresented in the indexed literature. This study presents a comprehensive bibliometric analysis of scientific publications on human embryonic development (2016–2026), integrating modern medical perspectives with Qur'ānic teachings to map scholarly output, identify dominant themes, and delineate gaps in interdisciplinary inquiry. A systematic search of the Scopus database using the query "human embryonic development" yielded 7,860 records. Metadata—including title, author, affiliation, publication year, source, keywords, and citation counts—were exported in CSV format and analysed using Biblioshiny in R-Studio to generate publication trends, country–author–keyword Sankey diagrams, and institutional affiliation maps. Data quality was excellent, with 0% missing data across core metadata fields. China and the United States were the dominant contributing nations; the University of California (n = 587), the University of Cambridge (n = 420), and the Chinese Academy of Sciences (n = 343) led institutional output. Research topics clustered around molecular biology, genetics, and experimental animal models. Sankey diagrams confirm a critical gap: the absence of explicit integration between contemporary embryological science and Qur'ānic embryological terminology. Confluence analysis reveals that 'Alaqah (4.5/5.0) and Nutfah (4.0/5.0) exhibit the strongest correspondence with modern embryological stages. This study underscores the urgent need for interdisciplinary frameworks bridging biomedical science and Islamic theology. Its primary contribution is a bibliometric map identifying underexplored research opportunities—particularly the systematic alignment of Qur'ānic embryological terminology with modern morphological and molecular indicators.